2015
DOI: 10.1111/tbj.12541
|View full text |Cite|
|
Sign up to set email alerts
|

Delay in Presentation, Diagnosis, and Treatment for Breast Cancer Patients in Jordan

Abstract: Breast cancer is the most common cancer, and one of the leading causes of death for females in Jordan and many countries in the world. Studies have shown that delay in symptoms presentation, diagnosis or treatment would result in poor prognosis. There has been no published study from Jordan on delays in patient presentation, delays in diagnosis, or delays in treatment. Therefore, we conducted this study to assess these important quality indicators aiming to improve prognosis for breast cancer patients in Jorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
1
19
2
Order By: Relevance
“…The observed time interval was shorter in countries such as Thailand (Poum et al, ), Estonia (Innos et al, ) and Jordan (Abu‐Helalah et al, ) than observed herein, with medians of 12, 16, and 30 days, respectively. In Morocco (Maghous et al, ), Niger (Pace et al, ), China (Yau et al, ) and Uganda (Odongo et al, ), the delay exceeds 90 days.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The observed time interval was shorter in countries such as Thailand (Poum et al, ), Estonia (Innos et al, ) and Jordan (Abu‐Helalah et al, ) than observed herein, with medians of 12, 16, and 30 days, respectively. In Morocco (Maghous et al, ), Niger (Pace et al, ), China (Yau et al, ) and Uganda (Odongo et al, ), the delay exceeds 90 days.…”
Section: Discussioncontrasting
confidence: 42%
“…Abu-Helalah et al, 2016) than observed herein, with medians of 12, 16, and 30 days, respectively. In Morocco(Maghous et al, 2016), Niger(Pace et al, 2015), China(Yau et al, 2010) and Uganda…”
contrasting
confidence: 45%
“…Socioeconomic and demographic characteristics are known be important determinants of individual behavior when seeking and using health services 8,15 , and have been associated with delayed diagnosis of several types of cancer, including breast cancer [16][17][18][19] . However, Brazilian studies investigating the relation between individual characteristics and diagnosis-to-treatment interval delays in patients enrolled in cancer treatment unit programs are scarce 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Time to diagnosis, the interval time between the first clinical consultation and the time that BC is diagnosed and confirmed by the doctor, is critical in BC management (Caplan et al, 1996;Barber et al, 2004;Redaniel et al, 2015;Abu-Helalah et al, 2016). In Indonesia, about 60-70% women with BC appear to be already in an advanced stage (stage III-IV) when starting their treatments (Ministry of Health of the Republic of Indonesia, 2016).…”
Section: Introductionmentioning
confidence: 99%